OTHERNESS AND FAMILIARITY AT SCHOOL AND AT HOME. IMAGES OF TEENAGE IMMIGRANTS AND RE-IMMIGRANTS IN SELECTED NOVELS FOR THE YOUTH FROM THE EARLY TWENTY-FIRST CENTURY (AFTER 2004) - Gromadzka, Beata (Porównania, 2018)
The topic of the article is developed around three selected novels: a Polish, Slovenian and an English one. All novels are addressed to the youth. These novels are linked by characters, teenagers who are trying to find their place in a foreign culture and a hermetic environment. There are three circles taken into consideration in the comparison: home, school, and local. These are spaces that are important for the main characters as the influences and fights for dominance clash; where the discrimination Alien/Other is an easy label for a victim. The comparison of common themes: growing up, school, peers, fighting for a place in the group, search for their own purpose shows the similarities and differences in the recognition of such problems by the authors of the described novels.